Risk of invasive pneumococcal disease in patients with asplenia/hyposplenism: A nationwide population-based study in Korea, 2009–2018 - Ji-Man Kang; Eun Hwa Kim; Kyong Ihn; Inkyung Jung; Minkyung Han; Jong Gyun Ahn (International Journal of Infectious Diseases, 2020)
Objectives: We aimed to determine the incidence and relative risk (RR) of invasive pneumococcal disease (IPD) in patients with asplenia/hyposplenism, using a nationwide population-based database. Methods: From 2009 to 2018, all claimed cases of newly diagnosed asplenia/hyposplenism in the National Health Insurance Service in South Korea were included. The incidence and RR of IPD in asplenia/hyposplenism patients were investigated using the Korean Center for Disease Control criteria. Results: Fifty-seven IPD cases were identified among 21,376 patients with 82,748 person-years of exposure. The cumulative 8-year IPD incidence was 0.5%; 45.6% of the infections occurred within two years after an asplenia/hyposplenism diagnosis. The age-standardised incidence rate was 104.5 per 100,000 person-years (95% confidence interval [CI], 103.6–105.4). Patients aged <5 years had a 15.1-times higher risk of IPD than those aged ≥60 years (95% CI: 5.8–39.5, p < 0.0001). The RR of IPD was 32.0 times higher in patients with asplenia/hyposplenism than in the general population (95% CI, 21.7–47.0); the standardized incidence ratio was 17.9(95% CI, 11.8–26.0). Conclusions: This large population-based study highlights the high IPD incidence rate and RR in Korean patients with asplenia/hyposplenism. Increased awareness and effective prevention strategies are needed for these high-risk populations, especially children aged <5 years.